O problema da formação (bildung) em Sobre o futuro dos nossos estabelecimentos de ensino, de Nietzsche - Rodrigues, Eduardo José Lobo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
It is investigating the conferences, spoken by F. Nietzsche, entitled On the future of our Educations Institutions the problem of formation (Bildung) that is discussed by Nietzsche as a criticism of the German educational model. Such criticism seeks to highlight that educational institutions do not promote the formation of an authentic culture to young people, both in the system and the junior college, but a preparation for professional activities and the market system. The educational model of the German state tends to promote the extension and maximum magnification of culture, and the tendency to reduce, to the weakening of the culture itself. Nietzsche thus draws a distinction between professional institutions, these institutions for the necessities of life, and cultural institutions. The definition of culture proposed by Nietzsche departs from modern dogmas and principles, taking the idea of true and instinctive understanding of nature, the Greek model and the German neo-humanism.

Trata-se de investigar nas Conferências, pronunciadas por F. Nietzsche, intituladas Sobre o futuro de nossos estabelecimentos de ensino o problema da formação (Bildung) que é discutida por Nietzsche como uma crítica ao modelo educacional alemão. Tal crítica procura evidenciar que os estabelecimentos educacionais não promovem a formação de uma cultura autêntica aos jovens, tanto no sistema ginasial como no universitário, mas sim uma preparação para as atividades profissionais e para o sistema do mercado. O modelo de educação do Estado alemão tende a promover a extensão e à ampliação máxima da cultura, e a tendência à redução, ao enfraquecimento da própria cultura. Nietzsche propõe assim uma diferenciação entre as instituições profissionais, ditas instituições para as necessidades da vida, e as instituições de cultura. A definição de cultura proposta por Nietzsche se afasta dos dogmas e princípios modernos, tomando a ideia de compreensão verdadeira e instintiva da natureza, do modelo grego e do neo-humanismo alemão.
Keywords: Nietzsche, Friedrich Wilhelm 1844-1900; Educação; Estado; Cultura; Natureza - Estudo; Nature study